Editors' Choice—Highly Diastereoselective Anodic Fluorination of Organosulfur Compounds Based on Neighboring Participation. Issue 10 (21st June 2019) - Furuta, Shoji; Inagi, Shinsuke; Fuchigami, Toshio
Abstract : Highly diastereoselective and efficient anodic α-fluorination of phenyl, p -chlorophenyl, and 2-naphthyl 3, 3, 3-trifluoro-2-methoxypropyl sulfides was successfully carried out at platinum electrodes in Et3 N-nHF (n = 3–5)/MeCN to provide the corresponding α-fluorinated products in good yields, whereas the corresponding p -methoxyphenyl sulfide derivative gave much lower diastereoselectivity. On the basis of such marked substituent effects on the diastereoselectivity and a previous study of anodic methoxylation of related sulfides, as well as the X-ray analysis of the configuration of the major diastereomer of the electrochemically fluorinated β -naphthyl derivative, it was clarified that the high diastereoselectivity is attributable to the neighboring MeO group participation to the anodically generated cationic intermediate destabilized by an electron-withdrawing CF3  group.